Dietary patterns and age at natural menopause: Evidence from the UK Women's Cohort Study. (January 2021) - Dunneram, Yashvee; Greenwood, Darren C.; Cade, Janet E.
Highlights: Diets rich in red and processed meat were associated with a later menopause. Two different methods of assessing dietary patterns resulted in similar results. This is the first study to explore the age at menopause in relation to dietary patterns. Abstract: Objectives: To investigate prospective associations between dietary patterns and age of natural menopause. Study design and main outcome measures: Menopausal status was reported at two time points 4 years apart in the UK Women's Cohort Study (UKWCS). Diet of participants was measured using a 217-item food frequency questionnaire at baseline. Principal component analysis (PCA) and reduced rank regression (RRR) were used to derive dietary patterns for 13, 916 women. Cox proportional hazards regressions were used to estimate hazard ratios (HR) and 95 % confidence intervals (CIs) for each pattern in relation to age at natural menopause, adjusting for potential confounders. Results: Five patterns were identified from the PCA, labelled as: 'vegetables and legumes', 'animal proteins', 'fruits', 'fats and sweets' and 'low-fat products'. Three patterns were derived from RRR: 'sweets, pastries and puddings', 'low-fat dairy and meat', and 'red meat and processed meat'. Women who scored 1 standard deviation higher on the 'animal proteins' pattern were 6% more likely to experience a later natural menopause over the study (HR = 0.94, 95 % CI: 0.90–0.97) compared with those who scored lower. The 'red meat and processed meat' pattern similary predicted a 7% higher risk for a later menopause during the study (HR = 0.93, 95 % CI: 0.87–1.00) per 1 standard deviation. Conclusions: Women whose diets are highly loaded with animal proteins, as well as red and processed meats, are more likely to have a later natural menopause.